PENGARUH LATIHAN AKUT LARI 30 M TERHADAP PENINGKATAN FREKUENSI DENYUT NADI DAN PERNAFASAN PADA ATLET BOLA BASKET PUTRI SMPN 17 PEKANBARU - Randhi Sapta Yuana; Slamet Slamet; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research was conducted by the Basketball Team of Putri SMPN 17 Pekanbaru, bolabasket education curriculum is one of extracurricular activities that very excluded by the students. Extracurricular activities this bolabasket has been running well but still a lot also often happens when playing games. Obstacles include: often making the ball during an assault to the opponent's area, generally the frequency of the pulse and breathing, then the posture of the player who is under the players of the opponent. The purpose of this study is to know: "Effect of 30 m running exercise to increase the frequency of pulse and breathing on athletes basketball SMPN 17 Pekanbaru directed 10 people. Sampling technique using total sampling. Based on the results of this study, a test that produces tcalcount of 16.696 with ttable 1.833 then H_a accepted, at alpha (α) 0,05 level. It can be concluded that the exercise exercise run 30 m to increase the frequency of pulse and breathing in female basketball athletes SMPN 17 Pekanbaru. Based on the results of the above research, it can be concluded that the exercise trains run 30 m to increase the frequency of pulse and breathing on basketball athletes daughter of SMPN 17 Pekanbaru, which means 30 m acute exercise can be used to repeat the pulse and breathing.Keywords; Acute Exercise 30 Meters, Frequency Of Pulse And Respiratory Rate